035 Using simulation to enhance the skills of paediatric cardiorespiratory physiotherapists: a collaborative approach. (December 2018) - Broughton, E; Akers, E; Mercer, H; Wright, S; Balls, J; Griffin, S
Abstract : Background: Simulation based education (SBE) is an effective means of enhancing the clinical skills of physiotherapists. 1 However, there are currently no simulation courses catering for paediatric physiotherapists within our region. Using International peer-review with the Lady Cilento Hospital, Brisbane and in collaboration with the Royal Brompton Hospital, a cardiorespiratory course was developed. This was aimed at paediatric physiotherapists working within the acute setting. Methods: The one day course linked the successful Australian model of Simulated Learning in Paediatric Allied Healthcare (SLiPAH) to UK working practices. Technical aspects of acute care were layered with cases requiring clinical reasoning. Pause discuss and immersive scenarios were blended with focused lectures and innovative manikin verbal responses were utilised. The course ran twice at GOSH, reaching 23 candidates from Healthcare trusts across London. Results: 100% of candidates agreed that the course increased their confidence in managing the paediatric patient with acute cardiorespiratory compromise 100% of candidates found the day useful in providing an overview of current issues in paediatric cardiorespiratory physiotherapy care The following themes emerged from the feedback: Confidence in clinical reasoning Enhancing technical skills Familiarisation with current practices Updating knowledge. Conclusion: A simulated learning course model proved an effective vehicle for enhancing the confidence in practice of Paediatric Physiotherapists. This collaborative approach to course facilitation promoted a culture of shared expertise and experience amongst candidates and facilitators, encouraging fruitful discussion around best practices in acute paediatric physiotherapy. Next steps: Mapping the UK need, 2 courses are proposed: ICU/High dependency and DGH/Community; accommodating candidates from both acute and community settings. The collaborative model of facilitation is proposed for other regional Allied Health courses, supporting shared expertise across London clinical education networks. References: Berry, et al. Simulation-based training can improve on-call physiotherapists' clinical reasoning abilities and self-reported competency. The 4th European Congress of the ER-WCPT/Physiotherapy 2016;102S:eS67–eS282.